Blinding practices during acute point-of-care ultrasound research: the BLIND-US meta-research study. Issue 3 (11th November 2020) - Prager, Ross; Wu, Kay; Bachar, Roudi; Unni, Rudy R; Bowdridge, Joshua; McGrath, Trevor A; Thavanathan, Rajiv; Woo, Michael Y; McInnes, Matthew D F
Abstract : Objectives: Point-of-care ultrasound (POCUS) diagnostic accuracy research has significant variation in blinding practices. This study characterises the blinding practices during acute POCUS research to determine whether research methodology adequately reflects POCUS use in routine clinical practice. Design, settings and participants: A search for POCUS diagnostic accuracy studies published in Emergency Medicine, Anaesthesia and Critical Care journals from January 2016 to January 2020 was performed. Studies were included if they were primary diagnostic accuracy studies. The study year, journal impact factor, population, hospital area, body region, study design, blinding of the POCUS interpreter to clinical information, whether the person performing the POCUS scan was the same person interpreting the scan, and whether the study reported incremental diagnostic yield were extracted in duplicate by two authors. Descriptive statistics were provided and prespecified subgroup analysis was performed. Main outcome measures: The primary outcome was the number of studies that blinded the POCUS interpreter to at least some part of the clinical information. Secondary outcomes included whether the person performing the POCUS scan was the same person interpreting it and whether the study reported incremental diagnostic yield. Results: 520 abstracts were screened with 97 studies included. The POCUS interpreter was blinded to clinical information in 37 studies (38.1%), not blinded in 34 studies (35.1%) and not reported in 26 studies (26.8%). The POCUS interpreter was the same person obtaining the images in 72 studies (74.2%), different in 14 studies (14.4%) and not reported in 11 studies (11.3%). Only four studies (4.1%) reported incremental diagnostic yield for POCUS. Inter-rater reliability was moderate (k=0.64). Subgroup analysis based on impact factor, body region, hospital area, patient population and study design did not show significant differences after completing pairwise comparisons. Conclusions: Although blinding the POCUS interpreter to clinical information may be done in a perceived attempt to limit bias, this may result in accuracy estimates that do not reflect routine clinical practice. Similarly, having a different clinician perform and interpret the POCUS scan significantly limits generalisability to practice as it does not truly reflect 'point-of-care' ultrasound at all. Reporting incremental diagnostic yield from implementing POCUS into a diagnostic pathway better reflects the value of POCUS; however, this methodology was infrequently used. Trial registration number: The study protocol was registered on Open Science Framework (https://osf.io/h5fe7/ ).